Molecular assessment of pretransplant chemotherapy in the treatment of juvenile myelomonocytic leukemia. Issue 11 (26th July 2019) - Hecht, Anna; Meyer, Julia; Chehab, Farid F.; White, Kristie L.; Magruder, Kevin; Dvorak, Christopher C.; Loh, Mignon L.; Stieglitz, Elliot
Abstract: Background: Despite the intensity of hematopoietic stem cell transplantation (HCT), relapse remains the most common cause of death in juvenile myelomonocytic leukemia (JMML). In contrast to other leukemias where therapy is used to reduce leukemic burden prior to transplant, many patients with JMML proceed directly to HCT with active disease. The objective of this study was to elucidate whether pre‐HCT therapy has an effect on the molecular burden of disease and how this affects outcome post‐HCT. Procedure: Twenty‐one patients with JMML who received pre‐HCT therapy and were transplanted at UCSF were analyzed in this study. The mutant allele frequency of the driver mutation was assessed before and after pre‐HCT therapy, using custom amplicon next‐generation sequencing. Results: Of the 21 patients, seven patients (33%) responded to therapy with a significant reduction in their mutant allele frequency and were classified as molecular responders. Six of these patients received moderate‐intensity chemotherapy, one patient received only azacitidine. The 5‐year progression‐free survival after HCT of molecular responders was 100% versus 61% for nonresponders ( P  = .12). Survival of molecular nonresponders was not improved by use of high‐intensity conditioning, but patients were salvaged if they experienced severe graft versus host disease. There were no baseline clinical characteristics that were associated with response to pre‐HCT therapy. Conclusions: Despite the myelodysplastic nature of JMML, patients treated with pre‐HCT therapy can achieve molecular remissions. These patients experienced a trend toward improved outcomes post‐HCT. Importantly, molecular testing can be helpful to distinguish between responders and nonresponders and should become an integral part of clinical care.